Ecological Values of Mangrove Forest Ecosystem - Cecep Kusmana (Media Konservasi, 1996)
Research on quantification of ecological values of mangrove forest ecosystem are urgently needed, due to its importance as the basics for utilization and management of resources. From the ecological point of vlew, the main prohlem of mangrove ecosystem is rarity and inconsistency of data and limited accurate methods inquantifying ecological values of that ecosystem. Results show that mangrove has the significant ecological values on coastal ecosystem. However, there must be further research to determine the accurate potentials of ecological benefit? of mangrove forest ecosystem.